Stereotactic magnetic resonance-guided online adaptive radiotherapy of adrenal metastases combines high ablative doses with optimized sparing of organs at risk. (March 2023) - Hoegen, Philipp; Katsigiannopulos, Efthimios; Buchele, Carolin; Regnery, Sebastian; Weykamp, Fabian; Sandrini, Elisabetta; Ristau, Jonas; Liermann, Jakob; Meixner, Eva; Forster, Tobias; Renkamp, C. Katharina; Schlüter, Fabian; et al.
Abstract: Purpose/Objective: To evaluate the potential of stereotactic magnetic resonance-guided online adaptive radiotherapy (SMART) to fulfill dose recommendations for stereotactic body radiotherapy (SBRT) of adrenal metastases and spare organs at risk (OAR). Materials and methods: In this subgroup analysis of a prospective registry trial, 22 patients with adrenal metastases were treated on a 0.35 T MR-Linac in 5–12 fractions with fraction doses of 4–10 Gy. Baseline plans were re-calculated to the anatomy of the day. These predicted plans were reoptimized to generate adapted plans. Baseline, predicted and adapted plans were compared with regard to PTV objectives, OAR constraints and published dose recommendations. Results: The cohort comprised patients with large GTV (median 36.0 cc) and PTV (median 66.6 cc) and predominantly left-sided metastases. 179 of 181 fractions (98.9 %) were adapted because of PTV and/or OAR violations. Predicted plans frequently violated PTV coverage (99.4 %) and adjacent OAR constraints (bowel: 32.9 %, stomach: 32.8 %, duodenum: 10.4 %, kidneys: 10.8 %). In the predicted plans, the volume exposed to the maximum dose was exceeded up to 16-fold in the duodenum and up to 96-fold in the spinal cord. Adapted plans significantly reduced OAR violations by 96.4 % for the bowel, 98.5 % for the stomach, 85.6 % for the duodenum and 83.3 % for the kidneys. Plan adaptation improved PTV coverage from 82.7 ± 8.1 % to 90.6 ± 4.9 % (p < 0.001). Furthermore, recently established target volume thresholds could easily be fulfilled with SMART. No toxicities > grade II occurred. Conclusion: SMART fulfills established GTV and PTV dose recommendations while simultaneously sparing organs at risk even in a challenging cohort.